The Effect of Parenting Alliances and Demographic Characteristics on Nutritional Status in Children with Avoidant Restrictive Food Intake Disorder in Malang Regency, Indonesia - Prasetyo, Yoyok B.; Nursalam, Nursalam; Hargono , Rachmat; Ahsan, Ahsan; Kumboyono, Kumboyono (Jurnal Ilmiah Kesehatan, 2025)
Avoidant restrictive food intake disorder (ARFID) is an eating problem in children, causing nutritional deficiency, obstructing growth, and development. This study investigates the correlation between demographic characteristics and parenting alliance to nutritional status in children with ARFID in Malang Regency. This analytic observational study used a cross-sectional approach from December 2018 to March 2019. There were 245 respondents with multistage sampling. Parenting alliance was quantified using questionnaires, and the children's nutritional status was quantified using anthropometry, categorized based on Z-score weight-for-age. Data analysis used Pearson correlation coefficients and Multiple linear regression with α=0.05. The result showed no correlation between parenting alliance and children's nutritional status (p>0.05). The multiple linear regression analysis demonstrated that children's nutritional status was influenced by a child's age (β = -0.156, p=0.020) and the number of children in a family (β = -0.263, p=0.029). In conclusion, parenting alliance is not directly related to children's nutritional status in children with ARFID. Nevertheless, the child's age and the number of children in a family affect their nutritional status.